2014
DOI: 10.1146/annurev-virology-031413-085550
|View full text |Cite
|
Sign up to set email alerts
|

Viruses and the Microbiota

Abstract: Every surface of the human body is colonized by a diverse microbial community called the microbiota, yet the impact of microbiota on viruses is unclear. Recent research has advanced our understanding of how microbiota influence viral infection. Microbiota inhibit infection of some viruses and promote infection of other viruses. These effects can occur through direct and/or indirect effects on the host and/or virus. This review examines the known effects and mechanisms by which the microbiota influence mammalia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
125
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 142 publications
(129 citation statements)
references
References 88 publications
(95 reference statements)
1
125
0
3
Order By: Relevance
“…The role of intestinal commensals in modulating viral infections has been increasingly recognized in recent studies (7). In this study, we compared anti-infectious and immunomodulatory effects of G+, G− probiotics, and their combination on RV infection and immunity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of intestinal commensals in modulating viral infections has been increasingly recognized in recent studies (7). In this study, we compared anti-infectious and immunomodulatory effects of G+, G− probiotics, and their combination on RV infection and immunity.…”
Section: Discussionmentioning
confidence: 99%
“…Many factors, such as malnutrition, micronutrient deficiencies, and breastfeeding (35) are implicated in the lower efficacy of enteric vaccines in impoverished countries. In addition to the aforementioned factors, recent studies have also shown a role for the intestinal microbiota in modulating enteric viral infections and oral vaccine responses (6, 7). Ablation of the intestinal microbiota reduced the severity of RV infection and modulated RV induced adaptive immunity in mice (8).…”
Section: Introductionmentioning
confidence: 99%
“…To examine how intestinal microbes influence viral infection and transmission many investigators use mouse models of infection including antibiotic treated animals or germ-free mice; each approach has pros and cons (51, 52). Antibiotic treatment is relatively simple and inexpensive, but depletion of bacteria is incomplete and selective depending on the antibiotic(s) used.…”
Section: Promotion Of Enteric Viral Infection By Bacteriamentioning
confidence: 99%
“…Invariably, host defense against the pathogens or host cell damage antagonizes the intruders [5] [6] [7]. Damage to host cells occurs during invasion of bacteria and non-enveloped viruses, including Salmonella, Shigella, Listeria or Adenovirus, which disrupt phagocytic vacuoles and endosomes [8] [9].…”
Section: Introductionmentioning
confidence: 99%